NURSING MANAGEMENT IN THE CONTROL OF AVOIDABLE LOSSES OF IM-MUNOBIOLOGICAL PREPARATIONS - Vanessa Comassetto Oliveira; Cristiano Caveião; Fernanda Crosewski (Universidade Federal do Paraná, 2014)
Immunobiological preparations are thermolabile, requiring refrigeration from the production laboratory until their administration. This study aimed to quantify and identify the causes of avoidable losses of immunobiological preparations in Paraná state, for the period 2009 to 2012. This was a quantitative, retrospective, exploratory study, in which data were obtained using the database of the Information System for the Calculation of Immunobiological Preparations Used of Paraná. Total losses of immunobiological preparations due to avoidable causes were 3,437,552 doses, with 95% of the losses being vaccines of the basic vaccination program. Failures that occurred in the organization of the service and/or the nursing work process can be identified, as the losses were considered preventable. The nurse is the manager of immunization activities, therefore, it is imperative to update this professional through training and continuing education for an effective service in the control of vaccine-preventable diseases.